Birdwatcher profile in the Ria Formosa Natural Park - Costa,Andreia (2018)
In the Algarve the potential for birdwatching tourism is widely recognized, especially in the Ria Formosa Natural Park (RFNP). This study aims to describe birdwatchers’ profile in the RFNP. For this purpose, a survey was applied. The results show that the most frequent nationalities of birdwatchers are: British (39%), Dutch (17%) and Portuguese (17%). The majority of birdwatchers are male (55%) and married (57%). The average age is 50 years old. They are highly educated (74% have an academic degree). Concerning profession, the most frequent answer was retired (41%). Respondents are committed to the activity as the majority possess special equipment and practice birdwatching in vacations. This study also tests if nationality is related to other characteristics of the birdwatchers, by using the Kruskal-Wallis and the Chi-square tests. Overall, the results of this study highlight that regional management organizations should invest in developing birdwatching in the RFNP.